Untapped Potential of Local Brewery Brands in Their Communities - Cara Jolly; Quisto Settle; Laura Greenhaw; Ruth Inman; Dwayne Cartmell (Journal of Applied Communications, 2021)
The craft brewery industry is growing in the United States. Due to changes in state law over the past 10 years, craft breweries are a relatively new industry in Oklahoma. A unique aspect of craft breweries compared to larger breweries is that craft breweries tend to be grounded in their local communities. The purpose of this research was to understand how craft breweries in Oklahoma establish their brand with respect to their communities. Interviews were conducted with brewery personnel across Oklahoma, including participants from both more established and newer breweries. The breweries in this study were purposefully engaging in their communities and serving as a third space (i.e., a place that is not home or work that helps foster social capital between community members). Much of the breweries’ promotion came from customers’ word-of-mouth and peers in the Oklahoma craft brewery industry. Breweries were actively using local identifiers in the products and tap rooms to utilize place branding. Craft breweries were working with each other to foster the state’s craft brewery industry, which is considered coopetition (i.e., when organizations that could be seen as competitors also help each other). Future research is recommended that addresses the craft breweries in other states to assess their brands in their communities, how the use of local identifiers in branding are perceived outside of the breweries’ local communities, and how results of this study apply to other locally oriented food and agricultural industries.
Keywords: craft breweries; place branding; third space; social capital; coopetition